Something Resembling Hope: Notes on strategies for teaching Canadian social justice literature - Yoder, Amarou (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2013)
Members of a large, cross-Canada research project on using Canadian social justice literature in the classroom share strategies that teachers are using to teach some of these texts. Strategies range from multi-media projects to song adaptations. Texts and strategies suitable for different grade-levels are represented, and cover a range of subjects, from residential schools to Canada’s history of segregation.